Policy Specialisation: A Meta-Analysis of Abil Hasan's Thoughts Al-Mawardi in the Book of "Ahkam us-Shulthaniyah" - Jasmadi; Chairul Bariah; Erna Fitriani Hamda; Lasri Lasri; Juaris Juaris; Muhammad Yusuf Zulkifli; Ilham Ilham (Jurnal Ikhtibar Nusantara, 2024)
Policy specialisation is a concept developed in the application of knowledge and technical skills in a particular field to design and implement effective policies. This research has an urgency on the need to understand and apply the principles of policy specialisation in modern times, as well as to explore the relevance of classical thought in contemporary policy theory. The purpose of the research is to analyse the concept of policy specialisation and map the relevance of these principles with the thoughts of Abil Hasan Al-Mawardi in his book "Ahkam us-Shulthaniyah". This research uses a meta-analysis method with a literature study approach (Library Research) by reviewing various literature including classic works and contemporary research, in data collection is done by synthesising data from various secondary sources, such as books, journal articles, and policy reports, as well as primary data from historical documents. The results showed that 1) indicators of the principles of policy specialisation including technical expertise, specific issues, and division of tasks, in line with Abil Hasan Al-Mawardi's thoughts in "Ahkam us-Shulthaniyah" are still in line with many of the principles covered in the concept of Policy Specialisation. Al-Mawardi strongly emphasises the technical expertise of stakeholders in state administration, both a clear division of roles in government and consistency in the application of laws and policies; 2) Meta-analysis of Al-Mawardi's thought shows that although his work was written in the 11th century many of the principles of state administration put forward in the book "Ahkam us-Shulthaniyah" can be applied in contemporary policy design. Al-Mawardi's contribution provides the foundation (Policy Specialisation) of policy specialisation in public administration, especially in governance that requires high coordination and consistency. This research confirms that the integration between classical theory and modern policy can enrich the understanding and implementation of public policy and provide a solid basis for the development of contemporary policy theory and practice.